(The Effect of Nutrients Addition in Nata Production from Tempeh Processing Waste) - Sutrisniati, Dwi; Rosidi, Bakri; -, Solechan (Warta Industri Hasil Pertanian, 1999)
A study to find out the best condition of in processing of nata from tempeh industries liquid waste ha been conducted. the variables used are sugar content and type of nutriets. the addition of sugar was 3%, 4% and 5%, while thenutients used was urea. ZA and DAP. the nata product was abserved for moinsture contenrt, thicness, weight of nata and dietary fibre content. Organoleptic test was done on the product of nata in syrup. the result showed that using 5% sugar with 0.4% urea and 0.2% DAP nutrient give the best product. the products were well accepted by the panelist